Weight shapes the intestinal microbiome in preterm infants: results of a prospective observational study - Heida, Fardou H.; Kooi, Elisabeth M. W.; Wagner, Josef; Nguyen, Thi-Yen; Hulscher, Jan B. F.; van Zoonen, Anne G. J. F.; Bos, Arend F.; Harmsen, Hermie J. M.; de Goffau, Marcus C. (BMC microbiology, 2021)
The intestinal microbiome in preterm infants differs markedly from term infants. It is unclear whether the microbiome develops over time according to infant specific factors. We analysed (clinical) metadata - to identify the main factors influencing the microbiome composition development - and the first meconium and faecal samples til the 4th week via 16 S rRNA amplican sequencing. We included 41 infants (gestational age 25-30 weeks; birth weight 430-990 g. Birth via Caesarean section (CS) was associated with placental insufficiency during pregnancy and lower BW. In meconium samples and in samples from weeks 2 and 3 the abundance of Escherichia and Bacteroides (maternal faecal representatives) were associated with vaginal delivery while Staphylococcus (skin microbiome representative) was associated with CS. Secondly, irrespective of the week of sampling or the mode of birth, a transition was observed as children children gradually increased in weight from a microbiome dominated by Staphylococcus (Bacilli) towards a microbiome dominated by Enterobacteriaceae (Gammaproteobacteria). Our data show that the mode of delivery affects the meconium microbiome composition. They also suggest that the weight of the infant at the time of sampling is a better predictor for the stage of progression of the intestinal microbiome development/maturation than postconceptional age as it less confounded by various infant-specific factors.